2015
DOI: 10.1007/s10877-015-9756-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of variable arterial transducer level on the accuracy of pulse contour waveform-derived measurements in critically ill patients

Abstract: We know that a 10 cm departure from the reference level of pressure transducer position is equal to a 7.5 mmHg change of invasive hemodynamic pressure monitoring in a fluid-filled system. However, the relationship between the site level of a variable arterial pressure transducer and the pulse contour-derived parameters has yet to be established in critically ill patients. Moreover, the related quantitative analysis has never been investigated. Forty-two critically ill patients requiring PiCCO-Plus cardiac outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…A previous study also investigated the effect of variable arterial transducer level on APCA-derived SV measurements in critically ill patients, albeit using the pulse contour cardiac output (PiCCO) system. In that study, vertical elevation of the transducer by 20 cm in relation to the zero-reference level brought about a statistically significant increase in SV index, defined as SV divided by the patient’s body surface area, of approximately 10% compared with baseline ( 5 ). The difference in the degree of change in SV measurements between this study and ours might be due to the physical and hemodynamic status of the patients and differences in the APCA devices used in the studies.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A previous study also investigated the effect of variable arterial transducer level on APCA-derived SV measurements in critically ill patients, albeit using the pulse contour cardiac output (PiCCO) system. In that study, vertical elevation of the transducer by 20 cm in relation to the zero-reference level brought about a statistically significant increase in SV index, defined as SV divided by the patient’s body surface area, of approximately 10% compared with baseline ( 5 ). The difference in the degree of change in SV measurements between this study and ours might be due to the physical and hemodynamic status of the patients and differences in the APCA devices used in the studies.…”
Section: Discussionmentioning
confidence: 91%
“…Arterial pulse contour analysis (APCA) provides real-time stroke volume (SV) measurements while being both minimally invasive and straightforward ( 4 ). Nonetheless, a recent study reported that the level of the arterial transducer may affect the accuracy of APCA-derived SV measurements ( 5 ). Hence, there is some concern that APCA may be affected during head-down tilting in the PLR test, as this action changes the zero-reference level of the transducer.…”
Section: To the Editormentioning
confidence: 99%
“…Invasive and minimally invasive PWA systems, thus, require optimal arterial catheter-derived arterial pressure waveforms. Arterial catheter-derived arterial pressure waveforms can be impaired by artifacts, incorrect levelling, or zeroing of the pressure transducer [40], and an inadequate dynamic response of the catheter-tubing-transducer system (underdamping or overdamping) [41,42]. Underdamping and overdamping may lead to incorrect identification of the dicrotic notch, which marks the transition from the systolic to the diastolic phase of the arterial pressure waveform and thus is indispensable for many PWA algorithms.…”
Section: General Limitations Of Pulse Wave Analysismentioning
confidence: 99%
“…Our study found when the transducer's vertical distance was >10 cm from the phlebostatic axis, the changes in continuous cardiac index reached statistical significance, and the change in the continuous cardiac index was >5% at the 15 cm variation of transducer and approximately 10% at 20 cm. [ 10 11 ] Some might argue that we could attach the transducer to a fixed level associated with the heart, but this practice might be difficult for femoral blood pressure monitoring and might require some special attached device. Second, the safety of tracheal tube or venous or arterial lines should be monitored when PLR is initiated from a semi-recumbent position.…”
Section: Hoice Of I Nitial P mentioning
confidence: 99%